Pancreatic Cancer : With Special Focus on Topical Issues and Surgical Techniques - Kim, Sun-Whe; Yamaue, Hiroki (Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book provides state of the art knowledge on a broad range of clinical issues in pancreatic cancer, covering topics from screening and pathophysiology to surgical treatments. In particular, the focus is on current controversies and on evidence-based surgical techniques. Further aspects considered include the management of precancerous lesions, diagnostic methods, perioperative care and nonsurgical treatment. The description of surgical methods is supported by many helpful illustrations and important technical issues are carefully addressed. Determination of resectability and extent of surgery is also discussed. Based on recent developments in surgical techniques, some surgeons are performing more and more radical operations. It is essential, however, that surgical strategy is based on the best available evidence and surgeons will find that this book offers valuable help in achieving this aim. In addition, it will be a great asset in clinical practice for all who are involved or interested in the management of pancreatic cancer.
Keywords: Medicine.; Radiology.; Pathology.; Surgery.; elektronické knihy; electronic books